1954
DOI: 10.1084/jem.99.6.505
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nature of Hemophilus Influenzae Cells Susceptible to Heritable Changes by Desoxyribonucleic Acids

Abstract: In E. influenzae the highly specific desoxyribonucleic acids (DNA's) which play the role of heredity determinants of type specificity and SM resistance, have induced these traits in only a small proportion of the population exposed to their action. The evidence suggests that this small proportion, "the susceptible cells" possess a property or substance needed by the DNA in order to induce an heritable change. The size of the small proportion of susceptible cells can be influenced significantly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
2

Year Published

1957
1957
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 11 publications
6
17
0
2
Order By: Relevance
“…The response of competent bacteria to eight different concentrations of DNA was examined in experiments with DNA preparations 2 and 4. Results for both str-r and type b antigen markers corresponded to those for streptomycin resistance reported by Alexander, Leidy & Hahn (1954) and by Goodgal (1961). Capsulated bacteria were observed in tests of 0-0001 pg.…”
Section: Delayed Multiplication Of Transformants 393supporting
confidence: 83%
“…The response of competent bacteria to eight different concentrations of DNA was examined in experiments with DNA preparations 2 and 4. Results for both str-r and type b antigen markers corresponded to those for streptomycin resistance reported by Alexander, Leidy & Hahn (1954) and by Goodgal (1961). Capsulated bacteria were observed in tests of 0-0001 pg.…”
Section: Delayed Multiplication Of Transformants 393supporting
confidence: 83%
“…Early studies, exploiting the natural transformability of H. injluenzae, demonstrated that a non-capsulated organism originally selected from a typed organism could be transformed to any other capsular types depending on the serotype of the organism from which the transforming DNA had been isolat~d (ALEXANDER et al 1954). Subsequent studies (CATLIN et al 1972) indicated that the locus for encapsulation (termed cap b) was located in the H. injluenzae chromosome near bio and that the cap b functions might be located over a segment of DNA as large as 50 kb.…”
Section: Genetics Of Haemophilus Influenza Capsulesmentioning
confidence: 99%
“…7, fasc. 4,1968 Assim, Xanthomonas campestris mostrou ser suscetível de so frer transformação genética bacteriana, quando ácido desoxiribonucleico extraído de uma linhagem resistente à estreptomicina e à eritromicina, transferiu os dois marcos genéticos para uma li nhagem sensível aos antibióticos.…”
Section: ) Transformação Bacteriana A)unclassified
“…7, fase. 4,1968 MATERIAL E MÉTODOS 1) Linhagem selvagem. O isolamento foi efetuado de ma terial enegrecido de vasos de caule de couve (Brassica oleraceae var.…”
unclassified